Bank Capital, Liquidity and Systemic Risk - Juergen Eichberger; Martin Summer (Oesterreichische Nationalbank (OeNB), 2004)
We analyze the impact of capital adequacy regulation on bank insolvency and aggregate investment. We develop a model of the banking system that is characterized by the interaction of many heterogeneous banks with the real sector, interbank credit relations as a consequence of bank liquidity management and an insolvency mechanism. This allows us to study the impact of capital adequacy regulation on systemic risk. In particular we can analyze the impact of regulation on contagious defaults arising from mutual credit relations. We show that the impact of capital adequacy on systemic stability is ambiguous and that systemic risk might actually increase as a consequence of imposing capital constraints on banks. Furthermore we analyze the indirect consequences of capital adequacy regulation that are transmitted to the real economy by their impact on equilibrium interbank rates and thus the opportunity costs of liquidity within the banking system.
Keywords: G21; G28; E44; 330; Capital Adequacy; Systemic Risk; Banking Regulation; Financial Stability